The Energy Ladder: A Valid Model for Household Fuel Transitions in Sub-Saharan Africa?. - Toole, Rebecca. (2017)
Abstract: This thesis explores the determinants of household cooking fuel use within the context of the energy ladder hypothesis. Rooted in economic theory, the hypothesis constructs a linear model of household energy use in developing countries. I draw on existing survey data assembled by the United States Agency for International Development (USAID) to construct a dataset of 26 sub-Saharan African countries. Using this, I assess the validity of the energy ladder in this geographical context. My analysis examines the relationship between wealth and cooking fuel use, as measured by the shares of households reporting the use of traditional, transitional or modern cooking fuels at the enumeration level, an administrative definition created for census sampling. I additionally test for the effects of other characteristics, such as asset ownership and demographic characteristics. Furthermore, I explore the differences in effects between rural and urban areas. I conclude that wealth is not the sole influencer of cooking fuel choice.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Mary Davis, and Ujjayant Chakravorty.; Keywords: Economics, Energy, and Sub Saharan Africa studies.